Management and Influence of Media in Crisis Situations of Enterprises - Aleksandra Vidovic; Відовіч Олександра; Vidović A. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. Well-organized channels of communication, which ensure a fast and efficient flow of information, form the basis for the development of positive relations at different management levels in the company. An attempt at balance in crisis situations boils down to playing with the media. Does the media play with the crisis or does it shape and define them? On this, a credible answer to the question could be given by participants in the media, as well as certain groups who have the opportunity to cooperate with them. There is no company that was not affected by the crisis. How long the crisis situation lasts depends on management, stakeholders, the public, relations with the media, the general state of the economy, the environment, and a number of factors, which appear sporadically demanding an effort to find a way out of the crisis. A crisis is essentially an event with potential negative consequences that affect the organization, company, industry, state, target public, products, services, and name. The media is responsible for the transmission of important information and strict attention must be paid to foreign parties’ communication, communication instruments, and communication functions. A parallel can be drawn here between communication and information because everything in the function of the media permeates perfectly and acquires a unique quality. From the other parties, celebrities, disguised advertising, and social networks represent one of the most common forms today of informing the general public about a product or service, today’syounger population. Crisis communication is an interactive process and can be defined as the exchange of information and opinions before, during, and after the outbreak of crisis situations. Marketing managers often know how to take advantage of unfavorable conditions in the economy, nature, and society by finding a solution to overcome certain problems. The aim of the research is to observe the influence of the media in the function of management in crisis situations of certain companies on the territories of Serbia, the Republic of Croatia, and Bosnia and Herzegovina as well as proposing measures on how to act in the future. The results of previous research in this area were used in the paper. The purpose of this research was to determine to what extent in the areas of the Republic of Croatia, Serbia, and Bosnia and Herzegovina, there is this form of influence as well as whether it is used as positive or negative publicity.

Резюме. Добре організовані канали зв'язку, які забезпечують швидкий і ефективний потік інформації, є основою для розвитку позитивних відносин на різних рівнях управління в компанії. Спроба балансування в кризових ситуаціях зводиться до гри зі ЗМІ. ЗМІ грають із кризою чи формують і визначають їх? На це запитання достовірну відповідь не змогли б дати учасники ЗМІ, а також окремі групи, які мають можливість з ними співпрацювати. Немає підприємства, якого б не торкнулася криза. Тривалість кризової ситуації залежить від менеджменту, стейкхолдерів, громадськості, відносин із ЗМІ, загального стану економіки, навколишнього середовища та ряду факторів, які епізодично виникають і вимагають зусиль для пошуку виходу з кризи. По суті, криза — це подія з потенційно негативними наслідками, які впливають на організацію, компанію, галузь, державу, цільову аудиторію, продукти, послуги та ін. Засоби масової інформації відповідають за передачу важливої інформації, тому слід приділяти особливу увагу комунікації іноземних сторін, інструментам комунікації та функціям комунікації. Тут можна провести паралель між комунікацією та інформацією, оскільки все у функції ЗМІ ідеально проникає і набуває унікальної якості. З іншого боку, знаменитості, прихована реклама та соціальні мережі є одними з найпоширеніших сьогодні форм інформування широкого загалу про продукт чи послугу, сучасну молодь. Кризова комунікація — це інтерактивний процес, який можна визначити як обмін інформацією та думками до, під час і після спалаху кризових ситуацій. Менеджери з маркетингу часто вміють скористатися несприятливими умовами в економіці, природі, суспільстві, знайшовши рішення для подолання певних проблем. Метою дослідження є спостереження за впливом засобів масової інформації на функцію управління в кризових ситуаціях певних компаній на території Сербії, Республіки Хорватії та Боснії та Герцеговини, а також запропонувати заходи щодо дій у таких ситуаціях у майбутньому. У роботі використано результати попередніх досліджень у цій галузі. У дослідженні поставлено задачу визначити, якою мірою на території Республіки Хорватії, Сербії та Боснії та Герцеговини існує ця форма впливу, а також як вона використовується як позитивна чи негативна сторона публічності.

A jól szervezett kommunikációs csatornák, amelyek biztosítják a gyors és hatékony információáramlást, alapját képezik a pozitív kapcsolatok kialakításának a vállalat különböző vezetői szintjein. A válsághelyzetekben az egyensúlyra való törekvés a médiával való játékban merül ki. A média játszik-e a válsággal, vagy formálja és meghatározza őket? Erre a kérdésre hiteles választ tudnának adni a média szereplői, illetve bizonyos csoportok, akiknek lehetőségük van együttműködni velük. Nincs olyan cég, amelyet ne érintett volna a válság. A válsághelyzet meddig tart, az a menedzsmenttől, az érintettektől, a nyilvánosságtól, a médiával való kapcsolatoktól, a gazdaság általános állapotától, a környezettől és számos olyan tényezőtől függ, amelyek szórványosan megkövetelik a válságból való kiutat. . A válság lényegében egy olyan esemény, amelynek potenciális negatív következményei lehetnek, amelyek érintik a szervezetet, vállalatot, iparágat, államot, célközönséget, termékeket, szolgáltatásokat és nevet. A média felelős a fontos információk továbbításáért, és szigorúan oda kell figyelni a külföldi felek kommunikációjára, kommunikációs eszközeire, kommunikációs funkcióira. Itt párhuzam vonható a kommunikáció és az információ között, mert a média funkciójában minden tökéletesen áthatol és egyedi minőséget nyer. A többi párt közül a celebek, az álcázott reklámok és a közösségi oldalak jelentik az egyik legelterjedtebb formát a nagyközönség, a mai fiatal lakosság tájékoztatásának egy termékről vagy szolgáltatásról. A válságkommunikáció egy interaktív folyamat, és úgy definiálható, mint a válsághelyzetek kirobbanása előtti, alatti és utáni információ- és véleménycsere. A marketingmenedzserek gyakran tudják, hogyan tudják kihasználni a gazdaság, a természet és a társadalom kedvezőtlen körülményeit úgy, hogy megoldást találnak bizonyos problémák leküzdésére. A kutatás célja, hogy megfigyelje a média befolyását a menedzsment szerepére egyes vállalatok válsághelyzeteiben Szerbia, a Horvát Köztársaság, valamint Bosznia-Hercegovina területén, valamint javaslatokat tegyen intézkedésekre a jövő. A cikkben az ezen a területen végzett korábbi kutatások eredményeit használtuk fel. A kutatás célja annak megállapítása volt, hogy a Horvát Köztársaság, Szerbia és Bosznia-Hercegovina területén milyen mértékű a befolyás ilyen formája, illetve azt, hogy ezt pozitív vagy negatív publicitásként használják fel.
A tömegtájékoztatás hatása a vállalkozások irányítására válsághelyzetekben
Управління та вплив ЗМІ в кризових ситуаціях підприємств
Редакційна колегія: https://aab-economics.kmf.uz.ua/aabe/about/editorialTeam
Зміст: https://aab-economics.kmf.uz.ua/aabe/issue/view/5
Keywords: management; enterprise; media; communication; propaganda; crisis